2021
DOI: 10.3390/su13147768
|View full text |Cite
|
Sign up to set email alerts
|

Shade-Grown Coffee in Colombia Benefits Soil Hydraulic Conductivity

Abstract: Secondary tropical forests and coffee agroforestry systems contain fewer trees than native forests but can positively impact soil hydrological functions, such as water infiltration compared to the pasture land that they replace. However, for both land uses it remains in how far the soil hydraulic characteristics are comparable to that of native forest. Therefore, we investigated the saturated hydraulic conductivity (Ks) and some hydrophysical soil attributes in four land-use types: (i) a shade-grown coffee; (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
2
7
1
Order By: Relevance
“…Not unexpectedly, the highest K s values were found at the RF, which was also the site with greater values for the vegetation attributes. This result is in line with many tropical studies that observed a high K s for little disturbed forests [7,19,20,22,33,52,53]. Overall, it is well documented in the literature that a good plant cover can generally prevent surface erosion, and a well-developed tree cover can also reduce shallow landsliding [3,15,54].…”
Section: Topsoil Properties and Vegetation Characteristicssupporting
confidence: 88%
See 3 more Smart Citations
“…Not unexpectedly, the highest K s values were found at the RF, which was also the site with greater values for the vegetation attributes. This result is in line with many tropical studies that observed a high K s for little disturbed forests [7,19,20,22,33,52,53]. Overall, it is well documented in the literature that a good plant cover can generally prevent surface erosion, and a well-developed tree cover can also reduce shallow landsliding [3,15,54].…”
Section: Topsoil Properties and Vegetation Characteristicssupporting
confidence: 88%
“…The top soil infiltration in the RF could be being influenced by occasional crossing of cattle, which can affect the runoff process. Our mean K s in the RF (324 mm h −1 ) site was lower than the mean reported value of 469 mm h −1 in a previous study [33] for a secondary old-growth forest that was more than 50-years-old. In that study, K s was also measured in a forest with 15 years of natural regeneration, showing a mean value of 244 mm h −1 , interestingly this value was similar with the mean K s in the AR (240 mm h −1 ), which can be interpreted as a recovery after a certain degree of degradation [55].…”
Section: Topsoil Properties and Vegetation Characteristicscontrasting
confidence: 88%
See 2 more Smart Citations
“…(2012) and Lozano‐Baez et al. (2021), whereas a ring insertion depth of 2 cm was reported by Hoeffner et al. (2021).…”
Section: Introductionmentioning
confidence: 90%